Implementasi Akad Murabahah Pada Produk Pembiayaan Kredit Pemilikan Rumah (KPR) di Bank Syariah Mandiri KC Bojonegoro Menurut Hukum Ekonomi Syariah - Anis Muhtarom (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
This study discusses about how the implementation of the murabahah bil wakalah contract theory on mortgage products in the Bank Syariah Mandiri KC Bojonegoro is seen from the perspective of Sharia Economic Law. The scope of this research is limited to the following issues: (1) How is the implementation of the murabahah contract on mortgage loans in Bank Syariah Mandiri KC Bojonegoro? (2) How is the implementation of the murabahah contract on mortgage loan products in the Bojonegoro KC Mandiri Syariah Bank according to the Sharia Economic Law? This research includes the type of field research. Because this research was conducted at Bank Syariah Mandiri KC Bojonegoro. This research is a qualitative descriptive study because in this study the author will focus the discussion on legal facts in the form of the implementation of financing between banks and customers with murabahah contracts which will then be continued with a comparative analysis of the legal facts referred to as sharia economic law theories. This is intended to test the compatibility between legal theory and the legal practice in question.The results of this research include: (1) The mechanism that must be taken to be able to receive financing for Public Housing Loans from Bank Syariah Mandiri KC Bojonegoro, is carried out through predetermined stages including: (a) submission; (b) BI checking / IDeb (debtor information); (c) the implementation of collateral estimates; (d) determination of ceilings; (e) Imputing data into a computer system; (f) approval of the official for mortgage loans; (g) Issuance of SP3 (Letter of Notification of Financing Approval); (h) Implementation of the contract which is attended by prospective customers, banks and notaries; (i) Disbursement. As for the agreements made between prospective customers and banks, there are elements as follows: (a) Contracting parties; (b) Sighat or iqab qabul akad murabahah; (c) Contract object. The object of the contract referred to in the housing loan product is a new or used house; (d) Nature of contract. Agreements are made clearly, both concerning objects, ceilings, time periods, contract places, financing nominal, margin obtained by the bank, and principal installments. In the event of default or bad credit where the customer is late in paying the installments, the bank's contribution will take the following steps: (a) Intensive billing; (b) Provision of Warning Letters 1, 2 and 3; (c) A restructuring offer (if the customer is pleased), ie installments are adjusted to the customer's ability and large at the end; (d) Voluntary guarantee selling offers; (e) Guaranteed auction. In a condition where the customer is not willing to carry out a contract restructuring, the bank offers that the auction of assets is a guarantee of the akah murabahah. As for the auction, the bank cooperates with a secret auction agency. (2) The implementation of housing loan financing with a murabahah contract in Bank Syariah Mandiri KC Bojonegoro is not in accordance with Sharia Economic Law originating from Law Number 21 of 2008 concerning Islamic Banking, MA Regulation Number 2 of 2008 concerning Compilation of Sharia Economic Law and DSN-MUI fatwa Number 4 of 2000 concerning Murabahah.Â Keywords: Contract, Murabahah bil Wakalah, KPR, BSM, Sharia Economic Law.Â